Adenosquamous carcinoma of the uterine cervix displaying tumor-associated tissue eosinophilia. (February 2019) - Kurose, Nozomu; Mizuguchi, Seiya; Ohkanemasa, Yoshiiku; Yamashita, Manabu; Nakano, Mariko; Guo, Xin; Aikawa, Akane; Nakada, Satoko; Sasagawa, Toshiyuki; Yamada, Sohsuke
Background: Tumor-associated tissue eosinophilia is defined as an inflammatory response with the marked infiltration of eosinophils within tumor tissues. Tumor-associated tissue eosinophilia has been reported in various organs; however, no studies have examined the detailed cytopathological findings of tumor-associated tissue eosinophilia. Case Presentation: A 49-year-old woman presented with lower abdominal and back pain that had started 1 month earlier. A cervical biopsy revealed a diagnosis of non-keratinizing squamous cell carcinoma. A mildly increased number of eosinophils was observed in both cervical cytology and a biopsy. On pelvic computed tomography, a tumor mass measuring up to 5.5 cm in the largest diameter was seen in the uterine cervix. After 1 month, endometrial cytology was performed, and non-keratinizing squamous cell carcinoma together with normal endometrial glands was obtained in a background of marked eosinophil numbers. Tumor cells in an irregular-shaped solid nest had variable-sized hyperchromatic nuclei and light-green-stained cytoplasm. The number of eosinophils was obviously increased. Considering the possibility of tumor-associated tissue eosinophilia, we evaluated a peripheral blood sample and confirmed an increased number of eosinophils. Radical hysterectomy was performed, and the final pathological diagnosis was adenosquamous carcinoma. Although the number of eosinophils decreased after surgery, it increased again at the time of recurrence 1 year later. Chemo-irradiation was performed, but the patient died 1 year and 8 months after the operation. Conclusion: Cytopathologists should consider the presence of tumor-associated tissue eosinophilia by focusing on not only tumor cells but also the markedly eosinophilic background. The eosinophil count might be a useful marker of the disease activity.